2022
DOI: 10.1186/s42234-022-00090-2
|View full text |Cite
|
Sign up to set email alerts
|

Sex-specific differences in the efficacy of traditional low frequency versus high frequency spinal cord stimulation for chronic pain

Abstract: IntroductionSpinal cord stimulation (SCS), an FDA-approved therapy for chronic pain, uses paresthesia (low frequency SCS (LF-SCS)) or paresthesia-free (such as high-frequency SCS (HF-SCS)) systems, providing analgesia through partially-elucidated mechanisms, with recent studies indicating a sexual dimorphism in pain pathogenesis (Bretherton et al., Neuromodulation, 2021; Paller et al., Pain Med 10:289–299, 2009; Slyer et al., Neuromodulation, 2019; Van Buyten et al., Neuromodulation 20:642–649, 2017; Mekhail e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In contrast, Slyer et al. reported that females were more likely to fail SCS therapy in the setting of concomitant depression, while Conic et al reported gender related outcomes differences in traditional versus high‐frequency SCS 54,55 . Odonkor et al 53 .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In contrast, Slyer et al. reported that females were more likely to fail SCS therapy in the setting of concomitant depression, while Conic et al reported gender related outcomes differences in traditional versus high‐frequency SCS 54,55 . Odonkor et al 53 .…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly studied variables are related to patient characteristics (age and gender), obesity/ BMI, diabetes, polysubstance use, psychological factors (depression, anxiety, and pain catastrophizing), history of spinal surgery, pain etiology (duration, type, and diagnosis), pre-operative disability levels, opioid use, and others. 36,41,43,45,[47][48][49][50][51][52][53][54][55][56]58,61,62 Despite increased awareness and research efforts to recognize these, the evidence T A B L E 5 Descriptive statistics on baseline opioid use in all subjects within the nonresponders and responders' group.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations